Policy Criminal Fines and Imprisonment Substitute Fines - Eddy Wibisono (The Southeast Asia Law Journal, 2016)
This research is motivated problems in policy implementation criminal fines and imprisonment substitute fines for criminal narcotics which are still being debated in the community. The method used in this study is a normative legal research conducted in an attempt to obtain the necessary legal materials in connection with the problem. Legal materials used are the primary legal materials, which consist of the Act and the judge's decision. Narcotics Act and court decisions relevant to the formulation of research problems have been studied to answer the formulation problems, and analysis using juridical methods. This study founded substitutes for policy implementation imprisonment penalty as a penal policy for the convict in the case of narcotic because it is a legal dictation.